2009
DOI: 10.1111/j.1398-9995.2009.02104.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergen IgE‐isotype‐specific suppression by maternally derived monoclonal anti‐IgG‐idiotype

Abstract: Idiotypic network reactivity is at least one major factor for induction of transgenerational IgE suppression by maternal IgG antibodies. If applicable to humans, these data suggest the possibility of a prophylactic and possibly therapeutic treatment of IgE-mediated allergic diseases with anti-idiotypic antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The importance of controlling the B cell repertoire is underscored by the observation that neonatal injection or maternally derived anti-idiotypic antibodies may induce a drastic distortion of the adult B cell repertoire (20, 21) and maternal anti-idiotypes can even induce a long-lasting transgenerational suppression of IgE responsiveness (22). However, these types of early imprinted responses typically involve B cells expressing specificities directed against antigens encountered early in life.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of controlling the B cell repertoire is underscored by the observation that neonatal injection or maternally derived anti-idiotypic antibodies may induce a drastic distortion of the adult B cell repertoire (20, 21) and maternal anti-idiotypes can even induce a long-lasting transgenerational suppression of IgE responsiveness (22). However, these types of early imprinted responses typically involve B cells expressing specificities directed against antigens encountered early in life.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [12,28,29,30,31] have demonstrated that maternal allergen-specific IgG, in particular IgG1, may cause suppression of allergen-specific IgE responses in the offspring. If maternal antibodies have this effect, then IgE suppression should wane after weaning when maternal IgG decreases in the offspring’s circulation.…”
Section: Resultsmentioning
confidence: 99%
“…In a mouse model, the maternally derived anti-id against allergen-specific IgE was shown to induce IgE suppression in the offspring which was long-lasting and dose-dependent. 37 As molecular modeling ruled out an internal image function of the anti-ids, possibly also here the binding to FcγRIIb could contribute to the protective function.…”
Section: The Functional Role Of Anti-ids In Allergymentioning
confidence: 99%